Evaluation Of Integrated Tuberculosis Program At Puskesmas Umbulharjo Yogyakarta With A System Approach - Nur Syarianingsih Syam; Desi Nurfita (Kesmas Indonesia, 2023)
Background: Tuberculosis (TB) is a public health problem that can cause high morbidity, disability and death. TB control is a form of shared commitment. The Indonesian government has a TB elimination target in 2030, with a case detection rate (CDR) in 2020 of 80%. The Information System is one of the tools used in TB control programs. The use of SITB in Puskesmas should be evaluated as a continuous improvement and an effort to provide TB control infrastructure in Indonesia. Purpose: The aim of this study was to evaluate using a systems approach, namely evaluating the input, process and output of using SITB at Puskesmas Umbulharjo. Methods: This research is a qualitative research with a case study approach. The data collection process was carried out in September - November 2022. The informants involved in this study were 5 people selected using a purposive sampling method. The process of collecting data using in-depth interview techniques. The data analysis used in the data processing is using the Miles and Huberman method where the data obtained is reduced, the data is presented, and conclusions are drawn. .Results: The evaluation used in this study is a system approach model, where the evaluation is assessed from the input, process and output variables. In the input variable, human resources or SITB users at the Puskesmas have received SITB training and the numbers are appropriate, namely there are SITB managers or admins, from the pharmacy department and the laboratory section, in terms of facilities, data processing facilities are available in the form of computers, discussion group facilities, network facilities. From a policy point of view, there is no SOP used for inputting and reporting data using SITB, and there is no budgeting of health funds for using SITB. The process of entering patient data is in accordance with the policy on using SITB, which starts from inputting TB suspect data, then requests for laboratory tests, service data provided for positive TB patients to filling in case history data. In the reporting process, the data that has been inputted is then analyzed to make monthly and quarterly report recaps. SITB reports are collected no later than the 10th. The output of SITB is in the form of TB incidence data, both TB SO and TB RO. SITB data is used in the decision-making process at the Puskesmas level. Conclusion: The use of SITB in terms of input is not optimal in terms of the availability of SOPs. Meanwhile, process variables are still not optimal in terms of recording and reporting processes. The SITB data output is good and used for decision making